Production of activated carbon from (EFB) for removal of cadmium - Al-Khatib, Ma'an Fahmi Rashid; Muyibi, Suleyman Aremu; Omotayo, Amode Jeminat (2010)
In this work, various activated carbons have been prepared by steam activation from oil palm empty fruit bunches to study the effect of activation temperature, activation time and steam flow rate. Series of batch laboratory experiments were conducted in order to investigate the feasibility of activated carbon – derived from oil palm empty fruit bunches to find the suitability of its application for the removal of heavy metal (cadmium) from aqueous solution through the adsorption process. Assessment was carried out by studying the influence of removal of Cadmium, pH, adsorbent dosage and agitation rate to select the optimum best production conditions using a 2-level full factorial experimental design for PACs produced.